The effect of Domino Card-assisted problem-based learning on elementary school students' responsibilities and learning outcomes - Elfrina Mayroja Pratika; Osa Juarsa; Endang Widi Winarni; Abdul Muktadir; Neza Agusdianita (Journal of Integrated Elementary Education, 2026)
The implementation of problem-based learning (PBL) assisted by domino cards has the potential to enhance elementary school students’ responsibility character and cognitive learning outcomes. This study aimed to examine the effect of PBL assisted by domino cards on students’ responsibility character and cognitive achievement. A quantitative approach with a quasi-experimental design was employed. The participants consisted of 63 fourth-grade students, with 31 students in the experimental group and 32 students in the control group. The groups were relatively homogeneous in terms of age, grade level, and academic ability. Data were collected through observation, pre-test and post-test, interviews, and documentation. The test instruments were piloted with 36 students to ensure validity and reliability. Data analysis involved descriptive statistics, prerequisite tests (normality and homogeneity), ANCOVA, and Pearson correlation analysis. The prerequisite tests indicated that the data were normally distributed and homogeneous. The ANCOVA results showed that PBL assisted by domino cards had a significant effect on students’ responsibility character (Sig. = 0.012; Partial Eta Squared = 0.100) and cognitive learning outcomes (Sig. < 0.001; Partial Eta Squared = 0.253). In addition, Pearson correlation analysis revealed a positive and significant relationship between responsibility character and cognitive learning outcomes (r = 0.463; Sig. = 0.009). These results imply that schools and educational stakeholders may consider implementing PBL supported by contextual media as an effort to improve learning quality and strengthen the Pancasila Student Profile, particularly the dimension of responsibility.